PEMANFAATAN PERMAINAN TRADISIONAL ENGKLEK SEBAGAI MEDIA PEMBELAJARAN GEOMETRI KELAS II DI SDN 01 KALIKUNING - Andhika Fajar Nugraha; Sugiyono; Suryatin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to describe the use of traditional engklek games as a geometry learning medium for second-grade students at SDN 01 Kalikuning, as well as to determine the obstacles faced in using traditional engklek games as a geometry learning medium. The type of research used is qualitative research. Descriptive research aims to describe or explain a phenomenon based on existing facts systematically, factually, and accurately. This study focuses on the use and obstacles of traditional engklek games as a geometry learning medium for second-grade students at SDN 1 Kalikuning. Data were obtained from observation, interviews, and documentation. The data analysis technique used is Miles and Huberman with three activities, namely, data reduction, data display, and conclusion drawing/verification. The results of the study show that traditional engklek games are proven to be an effective learning medium for lower-grade students, able to provide concrete learning experiences that are appropriate to their cognitive development stage. The use of traditional engklek games as a geometry learning medium for second-grade students at SDN 1 Kalikuning found several obstacles. Namely related to classroom conditioning carried out outdoors, the open environment causes distractions such as noise and other student activities that interfere with students' focus and concentration.